1044 Simple echocardiographic scoring in screening for aortic stenosis by emergency physicians in the emergency department. (17th January 2020) - Furukawa, A; Abe, Y; Miyaji, T; Hatakenaka, M; Naito, M; Ageta, K; Takeuchi, S; Morizane, A; Nishida, T; Ito, H
Abstract: Background; Aortic stenosis (AS) is one of the important critical diseases and may influence hemodynamics in cardiovascular or non-cardiovascular emergency, however, there is no established methodology to diagnose AS in a focused cardiac ultrasound (FOCUS). We have previously reported that our developed visual AS score was a simple index for AS screening using rapid echocardiography and it could successfully diagnose clinically significant AS. The purpose of the present study was to evaluate the diagnostic accuracy of visual AS score assessed by emergency physicians in the emergency department. Methods; Visual AS score was calculated as the sum of the scores of each three aortic cusp's opening in a short-axis view scored as follows: 0 = not restricted, 1 = restricted, or 2 = severely restricted; and classified in 0 – 6 as we previously reported. Emergency physicians who did not specialize in cardiology or ultrasonography underwent basic 30 minutes training to visualize aortic valve in a short-axis view and to assess visual AS score beforehand. They performed echocardiography and evaluated visual AS score in emergency outpatients with suspected cardiovascular diseases such as chest symptom, consciousness disorder, abnormal vital signs, heart murmur or abnormal electrocardiogram in the emergency department. Then, another assessment of visual AS score and complete echocardiography including quantitative assessment of AS was performed by expert sonographers. Aortic valve area index (AVAI) was calculated using continuity equation and body surface area, and an AVAI > 0.85 cm/m2, 0.6 - 0.85 cm/m2, and < 0.6 cm/m2 were defined as none or mild, moderate and severe AS, respectively. Results: Sixty patients underwent evaluations of visual AS score by emergency physicians. Visual AS score could not be assessed in 5 patients and continuity equation could not be evaluated in 2 patients, both due to poor echocardiographic imaging quality. Visual AS scores assessed by emergency physicians and expert sonographers showed strong positive correlation (R = 0.94, P < 0.0001). Fourteen patients (26 %) including 6 with shock or hypotension, 3 with congestive heart failure, 2 with syncope, 1 with acute myocardial infarction, 1 with suspected cardiac tamponade and 1 with abnormal electrocardiogram had moderate or more degree of AS in complete echocardiography performed by expert sonographers. Visual AS score 3 or more assessed by emergency physicians had 86 %, 100 %, 100 % and 95 % of a diagnostic sensitivity, specificity, positive predictive value and negative predictive value, respectively. Conclusion: Visual AS score in FOCUS is useful to screen for AS for emergency physicians who do not specialize in cardiology.